Lung Ultrasound Findings in Patients Hospitalized With COVID‐19. (5th March 2021) - Kumar, Andre; Weng, Yingjie; Duanmu, Youyou; Graglia, Sally; Lalani, Farhan; Gandhi, Kavita; Lobo, Viveta; Jensen, Trevor; Chung, Sukyung; Nahn, Jeffrey; Kugler, John
Abstract : Objectives: Lung ultrasound (LUS) can accurately diagnose several pulmonary diseases, including pneumothorax, effusion, and pneumonia. LUS may be useful in the diagnosis and management of COVID‐19. Methods: This study was conducted at two United States hospitals from 3/21/2020 to 6/01/2020. Our inclusion criteria included hospitalized adults with COVID‐19 (based on symptomatology and a confirmatory RT‐PCR for SARS‐CoV‐2) who received a LUS. Providers used a 12‐zone LUS scanning protocol. The images were interpreted by the researchers based on a pre‐developed consensus document. Patients were stratified by clinical deterioration (defined as either ICU admission, invasive mechanical ventilation, or death within 28 days from the initial symptom onset) and time from symptom onset to their scan. Results: N = 22 patients (N = 36 scans) were included. Eleven (50%) patients experienced clinical deterioration. Among N = 36 scans, only 3 (8%) were classified as normal. The remaining scans demonstrated B‐lines (89%), consolidations (56%), pleural thickening (47%), and pleural effusion (11%). Scans from patients with clinical deterioration demonstrated higher percentages of bilateral consolidations (50 versus 15%; P  = .033), anterior consolidations (47 versus 11%; P  = .047), lateral consolidations (71 versus 29%; P  = .030), pleural thickening (69 versus 30%; P  = .045), but not B‐lines (100 versus 80%; P  = .11). Abnormal findings had similar prevalences between scans collected 0–6 days and 14–28 days from symptom onset. Discussion: Certain LUS findings may be common in hospitalized COVID‐19 patients, especially for those that experience clinical deterioration. These findings may occur anytime throughout the first 28 days of illness. Future efforts should investigate the predictive utility of these findings on clinical outcomes.